CKD-Associated Pruritus and Dermatology-Related Quality of Life Among Hemodialysis Patients in Two Indonesian Hospitals: A Cross-Sectional Study - Risyda Ma'rifatul Khoirot; Tobi Pitora; Rahmawati Dian Nurani; Eva Riantika Ratna Palupi; Retno Tri Astuti Ramadhana; Sartika Rajagukguk (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2026)
Background: Chronic kidney disease (CKD) is a progressive condition that often requires maintenance hemodialysis. CKD-associated pruritus (CKD-aP), also known as uremic pruritus, is a distressing itching condition that remains under-recognized and may contribute to physical discomfort, sleep disturbance, psychological burden, and poorer dermatology-related quality of life. Objective: To examine the association between CKD-aP severity and dermatology-related quality of life among chronic kidney disease patients undergoing hemodialysis. Methods: This descriptive correlational cross-sectional study used purposive sampling. Data were collected from 72 hemodialysis patients at RSU Haji Surabaya and RSUD Sidoarjo during April-May 2019. Eligible participants were aged 18-65 years, received hemodialysis twice weekly, and reported pruritus within the previous month. Patients with primary dermatological conditions such as atopic dermatitis were excluded. CKD-aP severity was measured using the 5-D Itch Scale, and dermatology-related quality of life was measured using the Dermatology Life Quality Index (DLQI). Spearman's rank correlation was used for bivariate analysis. Results: The mean 5-D Itch Scale score was 14.83 +/- 4.224, and the mean DLQI score was 10.69 +/- 4.141. Because higher DLQI scores indicate poorer dermatology-related quality of life, the positive association between 5-D Itch Scale score and DLQI score indicated poorer outcomes with more severe pruritus. CKD-aP severity was significantly associated with dermatology-related quality of life (Spearman's rho = 0.588, p = 0.001, n = 72). Exploratory domain-level analysis suggested that pruritus degree (3.34 +/- 1.02) and duration (3.12 +/- 0.94) were the highest 5-D Itch Scale domains, while DLQI symptoms/feelings (3.11 +/- 1.38) and daily activities (2.41 +/- 1.21) were the most affected quality-of-life domains. Conclusion: This cross-sectional study found a significant moderate, approaching strong, positive association between CKD-aP severity and poorer dermatology-related quality of life among hemodialysis patients. Causality cannot be inferred. The findings support routine pruritus assessment and careful symptom management in hemodialysis nursing care